5(3x+13)+14x-17=

Simple and best practice solution for 5(3x+13)+14x-17= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3x+13)+14x-17= equation:


Simplifying
5(3x + 13) + 14x + -17 = 0

Reorder the terms:
5(13 + 3x) + 14x + -17 = 0
(13 * 5 + 3x * 5) + 14x + -17 = 0
(65 + 15x) + 14x + -17 = 0

Reorder the terms:
65 + -17 + 15x + 14x = 0

Combine like terms: 65 + -17 = 48
48 + 15x + 14x = 0

Combine like terms: 15x + 14x = 29x
48 + 29x = 0

Solving
48 + 29x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-48' to each side of the equation.
48 + -48 + 29x = 0 + -48

Combine like terms: 48 + -48 = 0
0 + 29x = 0 + -48
29x = 0 + -48

Combine like terms: 0 + -48 = -48
29x = -48

Divide each side by '29'.
x = -1.655172414

Simplifying
x = -1.655172414

See similar equations:

| mr=90-2q | | -9n(5n-1)=0 | | 4(x-5)=96 | | 12(4x+5)-8x= | | 2.6q-2.6-2.8q=-1.2q-1.9 | | 3x+65+4x+40=180 | | 10x+12=4x-17 | | 35x^2+38x=-8 | | G(5a+1)=-3x+5 | | 2.6q-2.6-2.8q=1.2q-1.9 | | M=9/2 | | c^3/5 | | 2x=[2+(-10)]x+20 | | -2=j-2/5 | | 5.57-5/12 | | 276=-16t^2+20t+300 | | 4+4r=r-5 | | 5(x-2)+13(x+11)= | | 0.5x+0.6(x+2)=3 | | 6v/2v | | 74=8*q | | -5x^2+16x-9=0 | | 5-2(x-1)=4+x | | -[9x+(7x+15)]=11-(21x+9) | | 36r+21t-t-37= | | 7z^2-30z+7z^2=0 | | .25x-x=m | | 3p^2=0 | | 3r-5=-11+4r | | 2x^4+x^2-28=0 | | -4.2=7c | | 3.5x-x=m |

Equations solver categories